Investigating The Impact Of Photovoltaic Connection To The Malaysian Distribution System - Mohd Zambri, Mohd Khairi; Mohd Aras, Mohd Shahrieel; Khamis, Alias; Hairi, Mohd Hendra (Penerbit Universiti, UTeM, 2016)
-